A Systematic Review of the Effectiveness of Algebraic Teaching Interventions: A Meta-Analysis and Meta-Synthesis - Sheree Sharpe; Matthew Mauntel; Rebecca Butler; Bitna Choi; Maryam Aswad; Jerome Amedu (Nordic Journal of Systematic Reviews in Education)
Algebra has long been recognized as a fundamental component of mathematics education for K-12 students and has been identified as a subject with which students continually struggle. Researchers have utilized various methods across contexts and conditions at the classroom level to improve algebra learning. This systematic review and meta-research (i.e., meta-analysis and meta-synthesis) aims to elucidate which of these efforts are effective, along with the conditions and populations for which they are most effective. In this article, we present our framing for the study under a modified version of the conceptual framework for learning progression, justify selected moderators, and detail our anticipated research process. Conducting meta-research on this topic is essential for providing policymakers, instructors, and researchers with an adequate understanding of the historical landscape of effective practices in algebra instruction.